A Systematic Review of Cardio-Metabolic Properties of Lonicera caerulea L. - Larisa Bora; Adelina Lombrea; Stefan Laurentiu Batrina; Valentina Oana Buda; Oana-Maria Esanu; Oana Pasca; Cristina Adriana Dehelean; Stefania Dinu; Zorita Diaconeasa; Corina Danciu (MDPI AG, 2024)
In the light of growing concerns faced by Western societies due to aging, natality decline, and epidemic of cardio-metabolic diseases, both preventable and treatable, new and effective strategical interventions are urgently needed in order to decrease their socio-economical encumbrance. The recent focus of research has been redirected towards investigating the potential of haskap (Lonicera caerulea L.) as a novel functional food or superfruit. Therefore, our present review aims to highlight the latest scientific proofs regarding the potential of Lonicera caerulea L. (LC), a perennial fruit-bearing plant rich in polyphenols, in reversing cardio-metabolic dysfunctions. In this regard, a systematic search on two databases (PubMed and Google Scholar) from 1 January 2016 to 1 December 2023 was performed, the keyword combination being Lonicera caerulea L. AND the searched pharmacological action, with the inclusion criteria consisting of in extenso original articles, written in English. The health-enhancing characteristics of haskap berries have been examined through in vitro and in vivo studies from the 35 included original papers. Positive effects regarding cardiovascular diseases and metabolic syndrome have been assigned to the antioxidant activity, hypolipidemic and hypoglycemic effects, as well as to the hepatoprotective and vasoprotective potential. Latest advances regarding LCF mechanisms of action are detailed within this review as well. All these cutting-edge data suggest that this vegetal product would be a good candidate for further clinical studies.